Analisis Framing pada Pemberitaan Kasus Pembunuhan Ferdy Sambo di Media Online Kumparan.com dan Tribunnews.com - Meita, Andini Dwi (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The media is not a free channel but has constructed the news in such a way. Some events are reported, some are not reported, some aspects are highlighted and some aspects are omitted, all of this leads to a concept called framing. This is related to the idea of Karim, et al. (2021) that efforts to instill character values can be one way to foster love for others. This study aims to see how Kumparan.com and Tribunnews.com framed the news of the Ferdy Sambo murder case at the official residence of Police officials in the Duren Tiga area, South Jakarta on July 11, 9, 10 August 2022. The results of this study are expected to be able to provide awareness to the public to love each other between human beings. Keywords: Framing Analysis, Zhondang Pankosicki, Media Reality Construction